2018
DOI: 10.1093/heapol/czy058
|View full text |Cite
|
Sign up to set email alerts
|

Measuring family planning quality and its link with contraceptive use in public facilities in Burkina Faso, Ethiopia, Kenya and Uganda

Abstract: The individual impacts of several components of family planning service quality on contraceptive use have been studied, but the influence of a composite measure synthesizing these components has not been often investigated. We (1) develop a composite score for family planning service quality based on health facility data from Burkina Faso, Ethiopia, Kenya and Uganda and (2) examine the influence of structural quality on contraceptive practice in these four countries. We used nationally representative cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 31 publications
2
60
0
1
Order By: Relevance
“…The quality of structural components of family planning services in public facilities (i.e. number of methods available, distance to facility) has been identified as an important factor in the adoption of modern contraception use in Ethiopia [15,18]. Nevertheless, studies have suggested that the quality and coverage of family planning counseling remains low in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of structural components of family planning services in public facilities (i.e. number of methods available, distance to facility) has been identified as an important factor in the adoption of modern contraception use in Ethiopia [15,18]. Nevertheless, studies have suggested that the quality and coverage of family planning counseling remains low in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…About 3% change in LAPMs use was due to the change in LAPMs use behavior among women who were visited by health workers. Studies in Ethiopia indicated that discussion about family planning with health workers was associated with increased LAPMs uptake [35,40]. The reason for this might be that when health workers visit home, they are more likely to provide detailed information about LAPMs.…”
Section: Discussionmentioning
confidence: 99%
“…The health care providers in a family planning perspective include nurses, clinical officers, HIV counsellors, and community health volunteers. The more the health care providers have been involved with counselling on family planning, the more the quality of counselling is affected [5]. The research disclosed a reduction in the quality of counselling in Burkina Faso, Ethiopia, Kenya and Uganda due to involvement of informal practitioners like community health workers.…”
Section: Literature Reviewmentioning
confidence: 96%
“…These countries were Ethiopia, Burkina Faso, Uganda and Kenya. The research was done by Fruhauf, Zimmerman, Kibira, Makumbi, Gichang, Shiferaw, Seme, Guiella, and Tsu [5] on calculating contraceptive excellence as well as its connection with contraceptive usage in municipal health care facilities in the four countries. In addition, the study indicated that quality of services and contraceptive use were compromised by an upsurge in informal providers offering contraceptive amenities.…”
Section: Literature Reviewmentioning
confidence: 99%